Pengaruh E-Service Quality dan E-Satisfaction terhadap E-Loyalty Pengguna Aplikasi Flip - Ricky Rohmanto; Jajang Suherman Jajang Suherman; Angelinaumi Khusnul Khotimah Angelinaumi Khusnul Khotimah; Ayi Mi’razul Mu’minin Ayi Mi’razul Mu’minin (Ma'soem University, 2026)
The growing utilization of digital financial services has driven the Flip application to evolve into one of the most widely used fintech platforms. Despite its rapid user growth, complaints remain regarding transaction speed and customer service responsiveness. This study aims to analyze the influence of E-Service Quality and E-Satisfaction on E-Loyalty among Flip users in the Cileunyi District. The research subjects consist of Flip application users residing in Cileunyi District. This study employs an associative quantitative method, with data collected through questionnaires and literature review. The sampling technique used is non-probability sampling with a purposive sampling approach, involving 100 respondents. The findings reveal that E-Service Quality has a significant effect on E-Loyalty, indicated by tvalue > ttable (10.654 > 1.984) and a significance value of 0.000 < 0.05, contributing 53.7% to user loyalty. Furthermore, E-Satisfaction also shows a significant effect on E-Loyalty with tvalue > ttable (12.311 > 1.984), a significance value of 0.000 < 0.05, and a contribution of 60.7%. Simultaneously, both variables significantly affect E-Loyalty with Fvalue > Ftable (85.229 > 3.09) and a combined contribution of 63.7%. These results indicate that the better the service quality and user satisfaction, the higher the level of user loyalty toward the Flip application.